Nutrient Intake and Nutrition Status in Vegetarians and Vegans in Comparison to Omnivores - the Nutritional Evaluation (NuEva) Study - Dawczynski, Christine; Weidauer, Thomas; Richert, Cora; Schlattmann, Peter; Dawczynski, Kristin; Kiehntopf, Michael (Frontiers in Nutrition, 2022)
Introduction: In recent years, vegetarian and vegan diets became increasingly important as they are associated with beneficial health outcomes. The NuEva study compares the impact of flexitarian, vegetarian, or vegan diets with omnivorous nutritional habits on nutrient intake and risk factors for non-communicable diseases. Methods: A dietary protocol was kept over five days and blood and 24h urine samples were collected to examine the impact of dietary habits (omnivores, n = 65 (Median / Interquartile range: 33 / 17 yrs.), flexitarians, n = 70 (30 / 17 yrs.), ovo-lacto vegetarians (28 / 14 yrs.), n = 65, vegans, n = 58 (25 / 10 yrs.)) on nutrient intake, nutrient concentrations in plasma, serum or 24h urine, body composition, and blood lipids. Results: The increased exclusion of animal based foods in the diet (omnivores < flexitarians < vegetarians < vegans) is associated with a decreased intake of energy, saturated fat, cholesterol, disaccha-rides, and total sugar as well an increased intake of dietary fibers, beta carotene, vitamin E and K. The combined index of the B12 status (4cB12 score) in vegetarians (0.02 / 0.75) was lower compared to omnivores (0.34 / 0.58; p ≤ 0.05) and flexitarians (0.24 / 0.52; p ≤ 0.05). In omnivores vitamin A, vitamin E, ferritin, and the urinary excretion of selenium, iodine, and zinc were higher than in vegans (p ≤ 0.05). In contrast, vegans had the highest concentrations of biotin, folate, and vitamin C. Flexitarians, vegetarians, and vegans had a lower body weight, BMI, and body fat percentage in comparison to omnivores (p ≤ 0.05). In omnivores the concentrations on total cholesterol, LDL cholesterol, LDL cholesterol/HDL cholesterol ratio, apolipoprotein B, and apolipoprotein B/ apolipo-protein A1 ratio were higher than in vegetarians and vegans (p ≤ 0.05). Conclusion: The NuEva study confirms the position of the Academy of Nutrition and Dietetics that adequately planned vegetarian diets are healthy, nutritionally adequate, and may provide health benefits in the prevention and treatment of non-communicable diseases. Nevertheless, critical nutrients were identified for all groups studied. This highlights the need to develop individual nutritional concepts to ensure an adequate nutrient intake.